Alternate‐day versus daily energy restriction diets: which is more effective for weight loss? A systematic review and meta‐analysis. (15th July 2016) - Alhamdan, B. A.; Garcia‐Alvarez, A.; Alzahrnai, A. H.; Karanxha, J.; Stretchberry, D. R.; Contrera, K. J.; Utria, A. F.; Cheskin, L. J.
Summary: Background: Alternate‐day‐fasting (ADF) has been proposed as an effective dieting method. Studies have found that it also can increase life span in rodents, and reduce inflammation in humans. The aim of this paper was to systematically review the efficacy of ADF compared to very‐low‐calorie dieting (VLCD) in terms of weight loss, and reduction of fat mass and fat‐free mass. Methods: Systematic review : PubMed literature searches were performed. Fixed review procedures were applied. Studies were evaluated for quality. Twenty‐eight studies were included. Meta‐analysis : 10/28 studies (four ADF and six matched VLCD) were further analyzed. Results: After adjustment for BMI and duration, there was no significant difference in mean body weight loss (VLCD 0.88 kg more weight loss than ADF, 95% CI: −4.32, 2.56) or fat‐free mass (VLCD 1.69 kg more fat‐free mass loss than ADF, 95% CI: −3.62, 0.23); there was a significant difference observed in fat mass (ADF 3.31 kg more fat mass loss than VLCD, 95% CI: 0.05, 6.56). Meta‐analysis showed that, among ADF studies, the pooled change in body weight, fat mass and fat‐free mass was 4.30 kg (95% CI: 3.41, 5.20), 4.06 kg (95% CI: 2.99, 5.13) and 0.72 kg (95% CI: −0.07, 1.51), respectively, while among VLCD studies, the pooled change was 6.28 kg (95% CI: 6.08, 6.49), 4.22 kg (95% CI: 3.95, 4.50) and 2.24 kg (95% CI: 1.95, 2.52), respectively. Conclusions: Our results from both the systematic review and the meta‐analysis suggest that ADF is an efficacious dietary method, and may be superior to VLCD for some patients because of ease of compliance, greater fat‐mass loss and relative preservation of fat‐free mass. Head‐to‐head randomized clinical trials are needed to further assess relative efficacy of these two approaches.